Developing the NIS solid density hydrostatic weighing system up to 20 kg - Hamdy Mohamed; Bayoumi Mohamed A.; Abuelezz Ali E.; Eltawil Alaaeldin A. (International Journal of Metrology and Quality Engineering, 2020)
This paper presents a developed design and construction to improve the performance and increasing the density measuring capability of the previous Hydrostatic Weighing Apparatus (HWA-NIS) at the National Institute of Standards (NIS) up to 20 kg. The previous (HWA-NIS) has been constructed up to 10 kg on 2014. The 2-Positions mass handler in the previous (HWA) was developed with 4-Positions pentagon shape to be able to make handling for individual masses in a group at once, when transferring the traceability from the primary standard “the Silicon Sphere” to the standard masses in the density scale weighing process. The weighing pan in the previous (HWA) was developed with four suspension wires with a diameter of 0.3 mm each, leads to reduce the surface tension affect on the measurement uncertainty by factor four times. The density of the standard masses in the range from 2 kg up to 20 kg were measured with an improved expanded uncertainty from 0.150 kg/m3 to 0.078 kg/m3 respectively due to reducing the effect of surface tension via the developed design of the weighing pan.